Dopamine D2 Receptor Density and Personal Detachment in Healthy Subjects - Breier, Alan; Kestler, Lisa; Adler, Caleb; Elman, Igor; Wiesenfeld, Neil; Malhotra, Anil; Pickar, David (The American journal of psychiatry, 1998)
Objective:The purpose of this study was to examine the relationship between the personality trait involving personal detachment and dopamine D2 receptor specific binding in healthy subjects.Method:Eighteen adult subjects completed the Karolinska Scales of Personality and the Tridimensional Personality Questionnaire and participated in a study that used [11C]raclopride positron emission tomography (PET) to quantify striatal D2 receptor binding. Results:A significant relationship was found between D2 receptor specific binding and detachment scores on the Karolinska Scales of Personality but not between D2 receptor specific binding and attachment scores on the Tridimensional Personality Questionnaire. In an exploratory analysis, the authors found a significant relationship between binding and the sentimentality cluster on the Tridimensional Personality Questionnaire but on no other personality clusters scores on the Tridimensional Personality Questionnaire or Karolinska Scales of Personality.Conclusions:These findings replicate those of a recent report that personal detachment scores on the Karolinska Scales of Personality are related to dopamine D2 receptor density and extends this finding by suggesting that the relationship is relatively specific to the trait defined by the Karolinska Scales of Personality and does not generalize to other forms of detachment. Am J Psychiatry 1998; 155: 1440-1442